2020
DOI: 10.3390/su12187428
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception on Purchase Decision Factors and Health Indicators Related to the Quality and Safety of Meat Sold in Dibiteries in Dakar, Senegal

Abstract: Accelerated socio-economic and demographic changes have led to the transformation of eating habits in sub-Saharan African cities including Dakar, Senegal. The result is the proliferation of informal fast-food establishments, such as the ‘dibiteries’ serving braised sheep meat. However, owing to poor hygiene practices, consumption of dibiterie meat poses a public health concern. It was unclear how the dibiterie meat quality and safety were perceived among customers who define their own purchasing social norms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 41 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…Previous studies have also reported that there are no differences between the formal and informal meat and milk value chains in the adoption levels of hygienic practices and practices (Minten et al, 2020;Seko et al, 2020). Low compliance and reluctance of meat and milk value chain actors to voluntarily and rigorously follow regulatory directives may be due to a lack of knowledge of the health and economic benefits of adopting these measures and a belief that adoption costs may exceed the derived benefits and poor enforcement of laws by officials (Nyokabi et al, 2018a;Seko et al, 2020). The presence of a large informal value chain with a heterogenous set of actors in Ethiopia complicates government efforts to enforce food safety regulations as laws do not currently take into account the differing sizes and contexts of actors (Vipham et al, 2018;Blackmore et al, 2022).…”
Section: Food Safety Risks and Management In Value Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported that there are no differences between the formal and informal meat and milk value chains in the adoption levels of hygienic practices and practices (Minten et al, 2020;Seko et al, 2020). Low compliance and reluctance of meat and milk value chain actors to voluntarily and rigorously follow regulatory directives may be due to a lack of knowledge of the health and economic benefits of adopting these measures and a belief that adoption costs may exceed the derived benefits and poor enforcement of laws by officials (Nyokabi et al, 2018a;Seko et al, 2020). The presence of a large informal value chain with a heterogenous set of actors in Ethiopia complicates government efforts to enforce food safety regulations as laws do not currently take into account the differing sizes and contexts of actors (Vipham et al, 2018;Blackmore et al, 2022).…”
Section: Food Safety Risks and Management In Value Chainsmentioning
confidence: 99%
“…Foodborne zoonoses negatively impact human health (Garedew et al, 2012;Cavalerie et al, 2021), with food serving as a medium for pathogen transmission if proper hygiene is not observed or implemented during the handling of ASF (Tigabu et al, 2015;Kumar et al, 2020). Previous studies have also reported that there are no differences between the formal and informal meat and milk value chains in the adoption levels of hygienic practices and practices (Minten et al, 2020;Seko et al, 2020). Low compliance and reluctance of meat and milk value chain actors to voluntarily and rigorously follow regulatory directives may be due to a lack of knowledge of the health and economic benefits of adopting these measures and a belief that adoption costs may exceed the derived benefits and poor enforcement of laws by officials (Nyokabi et al, 2018a;Seko et al, 2020).…”
Section: Food Safety Risks and Management In Value Chainsmentioning
confidence: 99%
“…This quality production could therefore allow an increase in the selling price of braised meat. Indeed, a recent study had shown that 84% of dibiterie meat consumers are ready to pay up to USD 0.84 more on the purchase prices to improve the defects of the dibiterie meat quality [ 35 ]. In addition, this price increase associated with the scale economy strategy (increasing returns to scale) could help to absorb these losses [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The perception of quality among dibiterie meat consumers is oriented towards organoleptic or sensory quality (taste, flavour, tenderness, etc.). Orou Seko et al [ 35 ] found that 61% of consumers were less concerned about health factors when buying braised meat in dibiteries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that risk aversion is the root cause of CISB [3,4], to reduce uncertainty and risk, consumers usually try to search relevant product information before buying [5], and as an important factor in delivering product quality and value, a product's price significantly affects consumers' perception of risk and plays a crucial role in their purchasing behaviors [6,7]. Scholars have conducted a large number of studies on the impact of price factor, which is usually the most important influencing factor for search behavior.…”
Section: Introductionmentioning
confidence: 99%